The anatomy of price gouging: A regulatory or competition law antidote - Njegovan Nikola; Ristić Bojan (Anali Pravnog Fakulteta u Beogradu)
Unlike other natural disasters, the coronavirus disease pandemic is global in character, which is why interest among researchers in the price gouging phenomenon is on the rise. Without disputing many solid arguments favouring the market mechanism, we will reconsider the goals and means of potential government intervention. One possibility lies in economic regulation, the other in competition law. In the first case, price ceilings are usually imposed for necessary goods, followed by rationing and export restrictions. On the other hand, competition policy focuses on preventing the exercise of temporary market power. We will try to show that market failures can provide specific arguments for regulation but relying on competition protection policy seems unjustified. Still, since the critical issue is defining excessive prices in the short run, we expect competition authorities to address this issue, considering that they are permanently monitoring various markets.